2022
DOI: 10.3390/ijms24010461
|View full text |Cite
|
Sign up to set email alerts
|

Blue-Green (~480 nm) versus Blue (~460 nm) Light for Newborn Phototherapy—Safety Considerations

Abstract: We have previously shown that the phototherapy of hyperbilirubinemic neonates using blue-green LED light with a peak wavelength of ~478 nm is 31% more efficient for removing unconjugated bilirubin from circulation than blue LED light with a peak wavelength of ~452 nm. Based on these results, we recommended that the phototherapy of hyperbilirubinemic newborns be practiced with light of ~480 nm. Aim: Identify and discuss the most prominent potential changes that have been observed in the health effects of photot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 104 publications
0
2
0
1
Order By: Relevance
“…Pergantian dari lampu fototerapi neon biru ke LED biru-hijau menimbulkan dampak yang baik untuk pengurangan waktu fototerapi, efek dari sinar fototerapi berkurang, paparan sinar lebih singkat terhadap peningkatan bilirubin tak terkonjugasi, pengurangan biaya fototerapi, dan pengurangan hari rawat inap (Ebbesen et al, 2022). Fototerapi LED lebih unggul daripada fototerapi CFL untuk penatalaksanaan hiperbilirubinemia neonatal.…”
Section: Pembahasanunclassified
“…Pergantian dari lampu fototerapi neon biru ke LED biru-hijau menimbulkan dampak yang baik untuk pengurangan waktu fototerapi, efek dari sinar fototerapi berkurang, paparan sinar lebih singkat terhadap peningkatan bilirubin tak terkonjugasi, pengurangan biaya fototerapi, dan pengurangan hari rawat inap (Ebbesen et al, 2022). Fototerapi LED lebih unggul daripada fototerapi CFL untuk penatalaksanaan hiperbilirubinemia neonatal.…”
Section: Pembahasanunclassified
“…Staphyloxanthin might also have an important implication in antibiotic resistance, as the pigment involves structuring a cell wall platform for the localization and functioning of penicillin-binding protein 2a (PBP2a) encoded by the mecA gene [6]. BL460 nm is believed to be safer for human cells than blue lights at other wavelengths [7]. Therefore, the BL460 nm has a high potential for practical implementation and is the subject of ongoing research.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperthermia and dehydration may occur during phototherapy, mainly in premature babies but also in full-term newborns, especially in non-LED photo devices [37]. The use of blue-green LED light may decrease the risk for hyperthermia, but may increase events of hypothermia [38]. On the other hand, the findings of Yassin et al showed that the use of LED phototherapy to treat premature jaundice increased the average incubator roof temperature by 2.9 • C and the indoor air temperature by 1 • C [39].…”
mentioning
confidence: 99%